METABOLIC SYNDROME IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: CLINICAL FEATURES, METABOLIC DISORDERS AND APPROACHES TO CORRECTION (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Metabolic syndrome (MS) combined with type 2 diabetes mellitus (T2DM) is one of the most urgent global health problems. It represents a cluster of metabolic and cardiovascular disorders such as abdominal obesity, hypertension, hyperglycemia, dyslipidemia, and insulin resistance [1–3]. The coexistence of MS and T2DM markedly increases the risk of cardiovascular events, nephropathy, and non-alcoholic fatty liver disease. According to IDF and WHO data, the prevalence of MS among diabetic patients reaches 60–80%, emphasizing the need for comprehensive therapeutic strategies to improve metabolic control and prevent complications.